Combinatorial effects of malaria season, iron deficiency, and inflammation determine plasma hepcidin concentration in African children - Atkinson, S; Armitage, A; Khandwala, S; Mwangi, T; Uyoga, S; Bejon, P; Williams, T; Prentice, A; Drakesmith, H (American Society of Hematology, 2014)
Hepcidin is the master regulatory hormone that governs iron homeostasis and has a role in innate immunity. Although hepcidin has been studied extensively in model systems, there is less information on hepcidin regulation in global health contexts where iron deficiency (ID), anemia, and high infectious burdens (including malaria) all coexist but fluctuate over time. We evaluated iron status, hepcidin levels, and determinants of hepcidin in 2 populations of rural children aged ≤8 years, in the Gambia and Kenya (total n = 848), at the start and end of a malaria season. Regression analyses and structural equation modeling demonstrated, for both populations, similar combinatorial effects of upregulating stimuli (iron stores and to a lesser extent inflammation) and downregulating stimuli (erythropoietic drive) on hepcidin levels. However, malaria season was also a significant factor and was associated with an altered balance of these opposing factors. Consistent with these changes, hepcidin levels were reduced whereas the prevalence of ID was increased at the end of the malaria season. More prevalent ID and lower hepcidin likely reflect an enhanced requirement for iron and an ability to efficiently absorb it at the end of the malaria season. These results, therefore, have implications for ID and malaria control programs.